2010
DOI: 10.1111/j.1600-0560.2010.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pruritic papules and plaques: a characteristic histopathologic presentation seen in a subset of patients with adult‐onset and juvenile Still's disease

Abstract: These cases confirm the characteristic clinical and histopathologic findings of 'persistent papules and plaques of Still's disease' and show the potential for this eruption in both the adult and juvenile age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 9 publications
(25 reference statements)
4
62
0
Order By: Relevance
“…9 This nonclassic variant also has unique histopathologic features including dyskeratosis in the upper layers of the epidermis extending into the stratum corneum without involvement of the basal layer and a superficial dermal infiltrate with neutrophils and lymphocytes. [4][5][6][7][8] While this nontypical variant was first described by Kaur et al 4 in 1994, it may be an underrecognized cutaneous manifestation of AOSD. In the largest case series of persistent pruritic papules and plaques published to date, Lee et al 6 found that 65% (11 of 17) of their patients with AOSD had this variant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 This nonclassic variant also has unique histopathologic features including dyskeratosis in the upper layers of the epidermis extending into the stratum corneum without involvement of the basal layer and a superficial dermal infiltrate with neutrophils and lymphocytes. [4][5][6][7][8] While this nontypical variant was first described by Kaur et al 4 in 1994, it may be an underrecognized cutaneous manifestation of AOSD. In the largest case series of persistent pruritic papules and plaques published to date, Lee et al 6 found that 65% (11 of 17) of their patients with AOSD had this variant.…”
mentioning
confidence: 99%
“…This variant manifests as nonevanescent pruritic erythematous papules and plaques with slight scale that often presents with a flagellate erythemalike presentation with linear configurations on the trunk and extremities. [4][5][6][7][8] The linearity may represent a Koebner phenomenon or scratching because the eruption characteristically spares the mid-back. Differential diagnosis of flagellate erythema includes bleomycin, dermatomyositis, and shiitake mushroom dermatitis.…”
mentioning
confidence: 99%
“…3, 4, 5). Recently, several papers show the unique histological features in the lesional skin of persistent pruritic papules and plaques [17][18][19][20][21][22][23][24][25][26]. Histopathology presents a characteristic pattern of dyskeratosis with a peculiar, distinctive distribution in (Fig.…”
Section: Persistent Pruritic Papules and Plaquesmentioning
confidence: 99%
“…Histopathology presents a characteristic pattern of dyskeratosis with a peculiar, distinctive distribution in (Fig. 6) [22][23][24][25]. A sparse cellular inWltrates containing neutrophils are seen in the upper dermis, but without vasculitis.…”
Section: Persistent Pruritic Papules and Plaquesmentioning
confidence: 99%
“…Further non-specific laboratory findings are inflammation-induced anaemia, leukocytosis and thrombocytosis [19]. Histopathology from lesional skin of urticarial autoinflammatory diseases like CAPS and sJIA reveals neutrophil-rich dermal infiltrates [37][38][39].…”
Section: Laboratory Findingsmentioning
confidence: 99%